Fertility, fiscal deficit, and sustainability of public debt in an endogenous growth model - Aso, Hiroki; Ueshina, Mitsuru (Economics and Business Review, 2023)
This aim of this study is to construct an overlapping-generations model to clear the effects of fiscal deficit on fertility. We reveal the relation between fiscal deficit and fertility and clarify the mechanism of fiscal deficit reducing fertility. Empirical evidence shows that an increase in debt-GDP ratio mitigated fertility. Our model indicates that fiscal deficit has positive and negative effects on fertility through the change of income tax rate. Numerical simulation shows that an increase in fiscal deficit reduces fertility. Therefore, this result is consistent with the empirical evidence. In addition, this study demonstrates that a steady state would not exist if child allowance for child-rearing costs would exceed the critical level. This result implicated that an expansion of the child allowance aimed for countermeasures to the falling birthrate can make sustainability of public debt unstable. Thus, countermeasures should be formulated to address the falling birthrate depending on the fiscal situation.